Arabidopsis EARLY FLOWERING 3 controls temperature responsiveness of the circadian clock independently of the evening complex. (26th October 2021) - Zhu, Zihao; Quint, Marcel; Anwer, Muhammad Usman
Abstract: Daily changes in light and temperature are major entrainment cues that enable the circadian clock to generate internal biological rhythms that are synchronized with the external environment. With the average global temperature predicted to keep increasing, the intricate light–temperature coordination that is necessary for clock functionality is expected to be seriously affected. Hence, understanding how temperature signals are perceived by the circadian clock has become an important issue. In Arabidopsis, the clock component EARLY FLOWERING 3 ( ELF3 ) not only serves as a light Zeitnehmer, but also functions as a thermosensor participating in thermomorphogenesis. However, the role of ELF3 in temperature entrainment of the circadian clock is not fully understood. Here, we report that ELF3 is essential for delivering temperature input to the clock. We demonstrate that in the absence of ELF3, the oscillator is unable to respond to temperature changes, resulting in an impaired gating of thermoresponses. Consequently, clock-controlled physiological processes such as rhythmic growth and cotyledon movement were disturbed. Genetic analyses suggest that the evening complex is not required for ELF3 -controlled thermoresponsiveness. Together, our results reveal that ELF3 is an essential Zeitnehmer for temperature sensing of the oscillator, and thereby for coordinating the rhythmic control of thermoresponsive physiological outputs. Abstract : We demonstrate that ELF3 is essential for temperature sensing of the circadian clock independently of the evening complex, and thereby for clock-mediated physiological processes such as diurnal growth.